A hybrid robust fault tolerant control based on adaptive joint unscented Kalman filter. (January 2017) - Shabbouei Hagh, Yashar; Mohammadi Asl, Reza; Cocquempot, Vincent
Abstract: In this paper, a new hybrid robust fault tolerant control scheme is proposed. A robust H ∞ control law is used in non-faulty situation, while a Non-Singular Terminal Sliding Mode (NTSM) controller is activated as soon as an actuator fault is detected. Since a linear robust controller is designed, the system is first linearized through the feedback linearization method. To switch from one controller to the other, a fuzzy based switching system is used. An Adaptive Joint Unscented Kalman Filter (AJUKF) is used for fault detection and diagnosis. The proposed method is based on the simultaneous estimation of the system states and parameters. In order to show the efficiency of the proposed scheme, a simulated 3-DOF robotic manipulator is used. Abstract : Highlights: A hybrid fault tolerant control scheme is proposed. A new adaptive joint unscented Kalman filter is introduced. The scheme is a combination of a robust H ∞ controller and Non-Singular Terminal Sliding Mode control. The proposed method is based on the simultaneous estimation of the system states and parameters. In order to show the efficiency of the proposed scheme, a simulated 3-DOF robotic manipulator is used.